The moderating effect of cultural restraint on the relationship between users’ motivations for following digital influencers on social media and subjective happiness - Hatamleh, Islam Habis Mohammad; Akkof, Alaa Makki Abdulhadi (Frontiers in Communication, 2025)
This study aims to discover the relationship between university students’ motivations for following digital influencers and their subjective happiness, combining a novel theoretical approach that integrates the Uses and Gratifications Theory (UGT) and Hofstede’s cultural dimension of restraint versus indulgence. Via a quantitative approach employing Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 650 Jordanian university students. Results showed a strong positive association between motivations for following digital influencers—including entertainment, escapism, information-seeking, self-expression, and social interaction—and subjective happiness. Additionally, cultural restraint significantly moderates this relationship, diminishing the positive impact of influencer-following motivations on subjective happiness in highly restrained cultural contexts. These findings offer critical insights into the nuanced chemistry between individual motivations, cultural values, and psychological well-being, emphasizing the importance of considering cultural restraint moderation effects in digital media research. Practically, the study provides essential guidance for content creators, educators, and policymakers aiming to enhance user well-being through culturally sensitive digital media strategies. This research significantly extends existing literature by demonstrating the pivotal role of cultural factors in shaping the psychological outcomes of digital influencer engagement.